Acid Uric 3× Tablet: Standardization and pharmacological evidence of uric acid use as anti-gout medicine - Ayisha Shaukat; Khalid Hussain; Nadeem Irfan Bukhari; Naureen Shehzadi (GarVal Editorial Ltda., 2020)
Context: Despite being a causative agent of gout, uric acid is used as an anti-gout medicine in homeopathy without reported scientific evidence, and such highly diluted medicines lack the exact amount of active ingredient per dose, which is mandatory for pharmacological evaluation. Aims: To determine active contents per tablet and evaluate anti-gout and anti-inflammatory activities of Acid Uric 3× Tablet, a homeopathic anti-gout medicine. Methods: A simple RP-HPLC method was developed and validated for the determination of uric acid in Acid Uric 3× Tablet. The standardized tablet was then investigated for anti-gout activity using xanthine oxidase inhibition and potassium oxonate-induced hyperuricemia in rats models. The tablet was also investigated for anti-inflammatory activity employing both in vitro and in vivo models. Results: The developed HPLC method was found to be simple, sensitive and precise. Acid Uric 3× Tablet was found to contain 250 µg uric acid/tablet. This medicine inhibited xanthine oxidase activity (IC50 = 12.42 μg/mL) and lowered the serum uric acid in tablet-treated rats (1.02 mg/dL) as compared to toxic group (4.87 mg/dL). The tablet also showed anti-inflammatory activity in heat-induced protein denaturation (IC50 = 4.6 ± 1.0 µg/mL), anti-proteinase (IC50 = 4.64 ± 1.0 µg/mL), heat-induced RBC hemolysis (IC50 = 12.39 ± 1.5 µg/mL) and hypotonicity-induced hemolysis (IC50 = 11.31 ± 1.0 µg/mL). Moreover, significant anti-inflammatory activity was found in the carrageenan-induced rat-paw edema model at a dose of 0.132 mg/kg. Conclusions: The findings of the study indicate that the developed HPLC method may be used to standardize Acid Uric 3× Tablet and provide scientific evidence of lowering uric acid level.